2013
DOI: 10.1021/ja4094132
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Mn(II) Hydration State in Metal Complexes and Metalloproteins through 17O NMR Line Widths

Abstract: Here we describe a simple method to estimate the inner-sphere hydration state of the Mn(II) ion in coordination complexes and metalloproteins. The linewidth of bulk H217O is measured in the presence and absence of Mn(II) as a function of temperature, and transverse 17O relaxivities are calculated. It is demonstrated that the maximum 17O relaxivity is directly proportional to the number of inner-sphere water ligands (q). Using a combination of literature data and experimental data for twelve Mn(II) complexes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 98 publications
12
138
1
Order By: Relevance
“…Caravan recently reported a method to estimate q (±0.2) on the basis of the experimental maximum 17 O transverse relaxivity (r 0 2max ) and a stand- ard value of the hyperfine coupling constant. [24] By using this approach, we estimated q = 0.8 ± 0.2, in perfect agreement with our hypothesis.…”
Section: O Nmr Relaxometric Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…Caravan recently reported a method to estimate q (±0.2) on the basis of the experimental maximum 17 O transverse relaxivity (r 0 2max ) and a stand- ard value of the hyperfine coupling constant. [24] By using this approach, we estimated q = 0.8 ± 0.2, in perfect agreement with our hypothesis.…”
Section: O Nmr Relaxometric Studiessupporting
confidence: 88%
“…[6,25] The crystallographic data revealed the formation of a dimeric [Mn(1,4-DO2A)] 2 complex in which the coordination geometry around each Mn II ion can be described as a distorted monocapped trigonal prism in which the two triangular faces formed by two ring N atoms and the carboxylate O atoms are nearly parallel (the distortion angle is 1.8°) and the capping positions are occupied by two bridging carboxylate O donor atoms. [24] The optimized geometries of the complexes [Mn(1,4-DO2A)] and [Mn(1,4-DO2A)(H 2 O)] obtained from DFT calculations highly resemble that found in the solid state, that is, a trigonal prism and a monocapped trigonal prism constructed from two parallel (the distortion angle is 5.4°) triangular faces defined by two ring N atoms and the carboxylate O atoms, respectively. [6] We assume that the predominant species of [Zn(1,4- 2+ obtained at 273 K, the signals associated with the protons of the cyclen ring give rise to unresolved multiplets, whereas an AB multiplet (-CH 2 -) and two singlets (-CH 3 ) are attributed to the protons of the acetamide pendant arms.…”
Section: Dynamic Nmr Studymentioning
confidence: 70%
“…46,47 The water exchange rate at 37 °C for [Mn(PyC3A)(H 2 O)] - is k ex = 1.0 × 10 8 s -1 ; associated kinetic parameters are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…31 Interestingly, it has also been shown that the rate of water exchange in various Ln(III) derivatives of MS-325 is quite sensitive to relatively minor structural differences between albumin from different mammalian sources 35 and when various Mn(II) complexes bind to albumin. 36 R1pobs=103×{false(r1f·c1false)+12false(r1cr1ffalse)×false(n·cHSA+c1+KA1false)false(n.0.2emcHSA+c1+KA1false)24·n·cHSA·C1false)}For the Zn(II) sensors presented here, HSA binding takes place mostly by the electrostatic interaction between the Zn(II)-DPA subunits and the tyrosine residue Y411 in the pocket site 2. 37 The binding affinity of each Zn(II) sensor to HSA was estimated by proton relaxation enhancement (PRE) titrations, a relaxometric technique commonly used to determine the dissociation constants ( K D = 1/ K A ) for binding of Gd(III) complexes to HSA.…”
Section: Resultsmentioning
confidence: 99%